Analisis Yuridis Terkait Putusan Hakim Dalam Perkara Penganiayaan Yang Menyebabkan Kematian Oleh Anak Berdasarkan Putusan Nomor 49/PID.SUS-ANAK/2023/PN.PLG - Rafli Tuada Yudha; Rustam (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Legal protection for children means protecting children from violence and ensuring their rights and welfare. Therefore, every child's right is protected to achieve the goal of creating a healthy young generation for the nation and the country. By using normative legal methodology. Assault that results in death is one type of crime in criminal law that has significant social and legal repercussions. This becomes even more complex when the perpetrators are children, who are governed by the Indonesian juvenile justice system. To gain a better understanding of the legal considerations made by judges and the consequences of those decisions on legal progress and child protection, a legal analysis of this ruling is necessary. The judge considers the psychological and social aspects of the perpetrator, who is a minor, in addition to the positive legal aspects